Meningkatkan Hasil Belajar Siswa Menggunakan Metode True or False - Made Ayu Pransisca; Munawir Gazali (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
Improving Student Achievement through active learning type true or false model at five grade Students (VC) at SDN 10 Montong Betok. This type of research is classroom action research. The objective of this research was to improve students’ achievement through active learning type true or false class VC IPS on SDN 10 Montong Betok. The researcher conducted two cycles of action research start from 10 April to 15 Oktober 2022. The subject of the research was students of class VC SDN 10 Montong Betok consisting of 24 students with details of 12 female students and 12 male students. The result of research that has been conducted shows that an increase in student learning achievement. this can be seen from the percentage of completeness learning achievement in cycle I of 37.5% increased to 87.5% in cycle II. Conclusion of this classroom action research is learning model, type active leaning true or false can improve students’ learning achievement in SDN 10 Montong Betok.